The Driving Force behind the Boom and Bust in Construction in Europe - Sun, Yan (IMF Working Papers; Working Paper ;, 2013)
This paper studies the factors behind pro-cyclical but widely varying construction shares (as a percent of GDP) across countries, with a strong focus on European countries. Using a dataset covering 48 countries (including advanced and emerging economies within and outside Europe) for 1990-2011, we find that country's geography, demographics, and economic conditions are the key determinants of a norm around which actual construction shares revolve in a simple AR(1) and error-correction process. The empirical results show that in many European countries, construction shares overshoot relative to their norms before the recent global crisis, but they have fallen significantly since the crisis. Nevertheless, there is still room for further adjustment in construction shares in some countries which may weigh on economic recovery.